READING OUR SOCIAL WORDS: UTILIZING NOVELS IN TEACHING SOCIOLOGY COURSES - Abd. Ghofur (IAIN MADURA, 2012)
This paper discusses the assignments used to analyze the novel using sociological concepts as well as the general outcomes. Students report enjoying the book and they are less hesitant to dig into difficult issues such as alcoholism, violence, sexuality, racism, and other forms of inequality. The ability to examine events on both macro- and microlevels improves over the course of the semester and students often integrate examples from the novels into class discussion and other assignments. The use of cultural artifacts such as film, poetry, music, or novels in sociology courses is certainly not a new phenomenon. As with other instructors, one of my main goals of using these types of materials, including novels, is to encourage active learning by students, as they are often comfortable working with these materials and can relate them to their own lives. Students are able to use their creativity and enhance their critical thinking skills when using cultural artifacts as tools of understanding sociological concepts. Novels in particular, offer a unique means to cover a wider range of social issues than can often be addressed in an introduction to sociology course. Another challenge of the course itself is to explore the complexities of diversity in society. Due to the pace of the course, students often maintain some sort of emotional or intellectual distance from the issues we examine, often discussing social issues as being outside of or disconnected from their own reality. Novels help to humanize the topics we cover as students often feel a connection with one or more main characters, which then helps them to apply the characters’ experiences to their own lives.